Europe's expansions and contractions : proceedings of the XVIIth Biennial Conference of the Australasian Association of European Historians (Adelaide, July 2009) - Australasian Association of European History. Conference 2009 : Adelaide); Smith, Evan B.; Australasian Association of European Historians (Unley, S.Aust. : Australian Humanities Press, 2010)
"The collection centres around the theme of Europe?s expansions and contractions that have occurred over the last five centuries and the profound way in which the idea of ?Europe? has shaped the globe. The collection spans a wide range of topics within this overall theme, with essays focusing on militarism in inter-war Germany, the Jewish diaspora, Australia?s migrant communities, Eastern European national identities, the shifting and lingering concept of European ?civilisation? and history, anthropology, post-colonialism and Marxism, and comparative empires." -- cover description.
Conference held at the State Library of South Australia, in July 2009.
Includes bibliographical references.
Keywords: Europe -- History -- Congresses